BASHAR AL ASSAD DAN KELOMPOK OPOSISI (Telaah Terhadap Konflik Suriah Pasca Arab Spring) - Mamdud, Rijal (LENTERA: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
Syria is one of the most important country in the Middle East. Political configuration in the Syrian government is highly fluid since a number of international powers have been trying to impose their agenda. Massive social unrest sweeping the whole Middle East, including Syria, has dramatically reshaped the social and political situation of modern Syria in the last decade. This paper, thus, aims at capturing the representation of conflict in Syria in the aftermath of massive social unrest known as arab springs by analyzing the current government of President Bashar al-Assad responses to the attempts of his overthrow by Syrian opposition party as well as by foreign powers.Â Keywords: Arab Spring, Syrian Conflict, Bashar al-Assad